2014
DOI: 10.1002/2014gl060404
|View full text |Cite
|
Sign up to set email alerts
|

On using the seasonal cycle to interpret extratropical temperature changes since 1950

Abstract: Extratropical near‐surface air temperature variability is explored on three different time scales: the seasonal cycle, observed changes in temperature since 1950, and the equilibrium response to increasing CO2 in an atmospheric general circulation simulation with fixed sea surface temperatures. Exploration is undertaken using an energy balance model (EBM) that parameterizes advective land‐ocean heat fluxes. The EBM is tuned only to the climatological seasonal cycle yet captures 47% of the variability in observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…If the macroweather-type behaviour over land held to longer timescales, internal variability would only play a minor role on the uncertainty of regional climate projections at multi-decadal and longer timescales 22,23 . However, a different scaling behaviour of ocean and land at longer timescales would imply an increasingly large variability discrepancy between terrestrial and marine regions, which seems physically implausible given their coupling by the atmosphere, and in contradiction with both diffusive energy balance models (EBMs) 24,25 and GCMs 17 . This leaves us with the conundrum that we must either reject altogether the marine proxies or see a fundamental change of variability in the terrestrial domain on longer timescales.…”
Section: Marine Influence On the Spatial Pattern Of Millennial Variab...mentioning
confidence: 99%
See 2 more Smart Citations
“…If the macroweather-type behaviour over land held to longer timescales, internal variability would only play a minor role on the uncertainty of regional climate projections at multi-decadal and longer timescales 22,23 . However, a different scaling behaviour of ocean and land at longer timescales would imply an increasingly large variability discrepancy between terrestrial and marine regions, which seems physically implausible given their coupling by the atmosphere, and in contradiction with both diffusive energy balance models (EBMs) 24,25 and GCMs 17 . This leaves us with the conundrum that we must either reject altogether the marine proxies or see a fundamental change of variability in the terrestrial domain on longer timescales.…”
Section: Marine Influence On the Spatial Pattern Of Millennial Variab...mentioning
confidence: 99%
“…EBMs suggest that this parallel behaviour of land and oceans on long timescales is due to heat exchange between the land and ocean compartments. In such models, land air temperature can be described as a linear combination of the SST and a time-dependent forcing over land 25,38 ; the resulting variability spectrum over land is then a linear combination of the spectra of each term (Fig. 1b) when the two are uncorrelated (Supplementary Note 2).…”
Section: Land-temperature Variability From Pollen Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way of achieving this is to use the Fourier transform method, which can transform temperature change in time to different frequencies and then use the 1 year frequency to characterize the annual temperature cycle (Prescott and Collins, 1951; Thomson, 1995; Stine et al ., 2009). Many researchers have studied the variations in the annual temperature cycle using observational data or model simulations that utilize the Fourier transform method and have found that the warming rate for winter is greater than for summer (Dwyer et al ., 2012; McKinnon and Huybers, 2014). A small phase delay and an amplitude increase in the annual surface air temperature cycle have been found at the global scale (Wallace and Osborn, 2002; Stine et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%